Prognostic Value of Clinical Biochemistry-Based Indexes in Nasopharyngeal Carcinoma - Zeng, Xiaojiao; Liu, Guohong; Pan, Yunbao; Li, Yirong (Frontiers in Oncology, 2020)
Inflammation and nutritional status have significant effects on the prognosis of cancer patients. This study investigated the predictive value of clinical biochemistry-based indexes in nasopharyngeal carcinoma (NPC). This retrospective study included 559 NPC patients and 500 patients with chronic rhinitis. Continuous variables were measured by t-test. The area under curves (AUC) was used to determine the diagnostic and prognostic value for NPC. Kaplan-Meier methods and the log-rank test were used to analyze overall survival (OS) and disease-free survival (DFS) of the patients. Cox and logistic regression analysis were used to analyze the independent prognostic risk factors for survival and influencing factors of side effects after treatment, respectively. The study results revealed that most indexes of NPC and rhinitis were significantly different between the two groups. In the survival analysis, the systemic inflammation score (SIS), prognostic nutritional index (PNI), albumin/globulin ratio (AGR), albumin (ALB), albumin-to-alkaline phosphatase ratio (AAPR), urea nitrogen (BUN) and creatinine (CREA) had significant influence on the OS and DFS. AGR was the optimal prognostic indicator for NPC. Among these indexes, SIS, AGR, BUN and CERA were independent prognostic factors of OS, AGR and PNI were independent prognostic factors of DFS. Most indexes were risk factors of side effects occurred in radiotherapy. In conclusion, the clinical biochemistry-based indexes, are reliable and of low-cost, therefore, they can be used in predicting diagnosis, prognosis and treatment plans of NPC.